Efficiency and Productivity of Zakat Management Organization during Covid-19 Pandemic: Evidence from National Scale ZMO - Syafaat Muhari; Hendra Kholid (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2026)
This study will analyze the management of ZIS funds from various national-scale ZMOs in terms of efficiency and productivity before, during, and after the pandemic throughout the period 2018 to 2022. The data source in this study is the ZMO financial report officially published on the website of each ZMO with a total of 14 ZMOs. The methods used in this study are Data Envelopment Analysis and Malmquist Total Productivity Index. From the results of this study, it can be seen that ZMO needs to improve its operational efficiency in both input and input components. In the input component, ZMO can minimize costs such as the use of amil funds, both labor and non-labor, as well as optimizing the use of fixed assets in order to obtain more optimal ZIS fund results.